Effect of deworming on cognitive performance of wral primary schoolchildren in Bachok, Kelantan. - Hamid, Anees Abdul; Ahmad, Zullkifli; Hassan, Mohd. Hashim Mohd (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2004)
Introduction: Previous studies have found that helminthiasis to be very common among school-aged children. This may be due to their outdoor activities, poor personal hygiene and poverty. Helminthiasis is also related to poor school performance. In this study, we are going to determine the effect of deworming on cognitive performance of rural primary school children in Kelantan. Method: This study was a community trial involving 600 schoolchildren in Bachok from 6 primary schools (aged between 9 and II years) was undertaken. The sampling frame involved all 17 rural primary schools in Bachok, Kelantan. Based on the sample size calculations, manpower and limitation of time, six schools were randomly selected with 728 schoolchildren. One-stage cluster sampling was used to choose the schools whereby all Standard 3 and Standard 4 children in the selected schools were recruited. At baseline, questionnaires on socioeconomic and health data related with helminthiasis were given, stool analysis and also cognitive performance tests was done. The cognitive tests administered to each child were the arithmetic test, coding test, digit span forward and backward tests. These three tests were taken from the Wechsler Intelligence Scale for Children. The other test given was the Raven's colored progressive matrices test. The schools were then randomly assigned into treatment and control group. Each child in the treatment group received 400mg albendazole while children in the control group were not given anthelmintic until the end of the study. After 6 months all of the cognitive tests were repeated. Results: A total of 728 children from 6 schools were invited to join this study. However, 600 children (82.4%) were enrolled, and 572 children (95.3%) completed the study after 6 months. There were 331 (55.2%) children aged 9-10 years and 269 (44.8%) children aged 10-11 years. There were 290 (48.3%) girls and 310 (51.7%) boys. The overall prevalence of total helminthiasis was 74.2% (n=445). Prevalence of Trichuris trichiuria, Ascaris lumbricoides and hookworms were 67.2% (95% CI: 63.4%, 70.9%), 49.7% (95%CI: 45.6%, 53.7%) and 1.2% (95°/oCI: 0.3%, 2.0%) respectively. On baseline examination, children with helminthiasis scored significantly lower than those uninfected in arithmetic test, coding test and Raven's colored progressive matrices test. However, in the digit span forward test and digit span backward test, even though the scores were lower in the infected children compared to those not infected, the differences was not statistically significant. Male children are 1.57 times more associated with helminthiasis compared to female students and children who having number of children in the house 5 and more were 2.54 times more associated with helminthiasis compared to those having number of children less than 5. Following deworming with albendazole, at 6 months, multivariate analysis using repeated measures ANOV A showed significant difference in the coding test (F 1 • 57 = 5.41,p=0.02 ) and the Raven's colored progressive matrices test (F 1,57 = 9.39, p=0.02) between the treated and control group. However, the digit span backward test, the aritlunetic test and digit span forward test were not significantly different in the 2 groups. After adjusting for infection status and family income, almost similar result were noted whereby, children in the treatment group had significantly higher scores for the coding (F t, 56 = 5.33, p=0.02) and Raven's colored progressive matrices tests ( F 1,56 = 10.1 0, p=O.OO) compared to the control group. However, for 3 other tests, arithmetic, digit span forward and digit span backward there were no significant different. Conclusion: Children who have helminthiasis have generally poorer cognitive performance. Gender and number of children in the family were significantly associated with helminthiasis. There were improvements in certain cognitive tests 6 months after children were given anthelmintic. Mass deworming with single doses of oral albendazole should be given to rural schoolchildren as it may improve some aspects of their cognitive performance.